Urban Governance in Haryana: Challenges, Institutional Capacity and Policy Reforms - Dr Rajvir Dhaka (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Rapid urbanization has emerged as a defining feature of India’s socio-economic transformation. Urban centres are increasingly becoming engines of economic growth, innovation and employment generation. However, the rapid expansion of cities has also created serious governance challenges related to infrastructure, service delivery, environmental sustainability and institutional capacity. Haryana, one of the fastest-growing states in northern India, has experienced significant urban expansion due to industrialization, migration and the growth of the National Capital Region (NCR). Urban Local Bodies (ULBs) are expected to play a central role in managing urban development and providing essential civic services. Despite the constitutional recognition provided by the 74th Constitutional Amendment Act, municipal institutions in Haryana continue to face several structural and administrative constraints. These include inadequate financial autonomy, weak revenue mobilization, shortage of skilled personnel, and limited planning capacity.